Relación entre liquidez y rentabilidad de las Cooperativas de Ahorro y Crédito de la Provincia de Chimborazo, periodo 2016 - Robayo Velasco, Jessica Caterine (2019)
The research project titled " RELATIONSHIP BETWEEN LIQUIDITY AND PROFITABILITY OF THE CREDIT UNIONS OF THE CHIMBORAZO PROVINCE, PERIOD 2016", was carried out based on the Credit Unions that report information to the Superintendence of Popular and Solidarity Economy SPSE. The purpose of this research has been to analyze the behavior of liquidity and profitability, to do it, it proceeded to analyze the financial indicators of these variables, which experienced variations during the study period. For its approach, it is necessary to explain that the applied methodology is based on the analysis and discussion of results, to accept the hypothesis that will be proven through an econometric model called Data Pool in three years with seven Credit Unions. Finally, this process can be inferred from the existence of a relationship between the variables. It will allow us to express conclusions and recommendations.